Comparison of computed tomography perfusion and magnetic resonance dynamic susceptibility contrast perfusion-weighted imaging in canine brain - Lee, Sangmin; Park, Soomin; Hong, Sungwha; Kim, Soyeon; Yoon, Junghee; Choi, Jihye (Frontiers in Veterinary Science, 2024)
Brain perfusion allows for the evaluation of cerebral hemodynamics particularly in brain infarcts and tumors. Computed tomography (CT) perfusion (CTP) provides reliable data however it has a limited scan field of view and radiation exposure. Magnetic resonance (MR) perfusion provides detailed imaging of small structures and a wide scan field of view. However, no study has compared CTP and MR perfusion and assessed the correlation between the perfusion parameters measured using CTP and MR perfusion. The aim of the present study was to assess the correlation and agreement of the cerebral perfusion derived from dynamic susceptibility contrast (DSC)-MRI and CTP in dogs. In this crossover design study, the cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time, and time to peak were measured in the temporal cerebral cortex, caudate nucleus, thalamus, piriform lobe, and hippocampus using CTP and DSC-MRI in six healthy beagle dogs and a dog with pituitary tumor. On the color map of healthy beagles, blood vessels and the perivascular brain parenchyma appeared red-green, indicating high perfusion, and the areas distant from the vessels appeared green-blue, indicating low perfusion levels in CTP and DSC-MRI. CTP parameters were highest in the piriform lobe (CBF = 121.11 ± 12.78 mL/100g/min and CBV = 8.70 ± 2.04 mL/100g) and lowest in the thalamus (CBF = 63.75 ± 25.24 mL/100g/min and CBV = 4.02 ± 0.55 mL/100g), respectively. DSC-MRI parameters also were highest in the piriform lobe (CBF = 102.31±14.73 mL/100g/min and CBV = 3.17 ± 1.23 mL/100g) and lowest in thalamus (CBF = 37.73 ± 25.11mL/100g/min and CBV = 0.81 ± 0.44 mL/100g), although there was no statistical correlation in the quantitative perfusion parameters between CTP and DSC-MRI. In a dog with pituitary tumor, the color map of the tumor revealed as red scale, indicating high perfusion and higher CBF and CBV on CTP (149 mL/100g and 20 mL/100g/min) as well as on DSC-MRI (116.3 mL/100g and 15.32 mL/100g/min) compared to those measured in healthy dogs, respectively. These findings indicate that DSC-MRI and CTP maps exhibit comparability and interchangeability in the assessment of canine brain perfusion.